A Postcolonial Criticism in Jane Eyre - Hendriani, Ria (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Jane Eyre was first published in 1847. It is a novel that in the 19th century contributed hugely to the colonial discourse and the depiction of the colonized other in terms of physical representation, stereotypes, and female agency. It was created during the age of the British colonial expansion at the time when Britain shifted its interest from the West Indies to the East. This paper aims at analyzing colonial issues included by Bronte in the novel. The paper will focus on analysis of the colonialist ideology, sexism, freedom, ethnicity, and injustice of Jane Eyre in the context of colonial discourse. And finally, a study of the colonial wealth and inheritance will be conducted. To do this, a historical and literary analysis of the text will be needed